Polymorphisms of a novel long non-coding RNA RP11-108K3.2 with colorectal cancer susceptibility and their effects on its expression. Issue 1 (March 2020) - Jiang, Danjie; Jin, Mingjuan; Ye, Ding; Li, Yingjun; Jing, Fangyuan; Zhang, Xiaocong; Li, Qilong; Chen, Kun
Background: RP11-108K3.2 was recently identified as a novel long non-coding RNA (lncRNA) transcript, and several single nucleotide polymorphisms (SNPs) have been identified in its coding region. This study aimed to explore the associations of tagSNPs in RP11-108K3.2 with the risk of colorectal cancer and their effects on its expression. Methods: A total of 821 colorectal cancer cases and 857 healthy controls were enrolled into this two-stage case-control study. Demographic characteristics and lifestyle information were collected by a validated questionnaire. Six tagSNPs were genotyped by using Sequenom MassARRAY platform. A total of 71 additional colorectal cancer cases were recruited, of which the genotypes of potential polymorphisms and the RP11-108K3.2 expression levels were determined. Results: In the discovery set, only the rs2470151 C/T polymorphism was found to have a promising association with the risk of colorectal cancer, and this polymorphism was further replicated in the validation set with a significantly decreased risk of colorectal cancer (adjusted odds ratio 0.73; 95% confidence interval 0.55, 0.97). Combined discovery set and validation set together, this negative association was found both in the heterozygote codominant model and the dominant model. Furthermore, colorectal cancer patients carrying rs2470151 CT/TT genotypes had a marginally lower RNA expression of RP11-108K3.2 than those carrying the CC genotype. Stratified analyses showed the association between rs2470151 and the risk of colorectal cancer were influenced by family history of cancer, smoking, alcohol consumption, and tea drinking. Conclusions: These findings suggest that RP11-108K3.2 rs2470151 had a significant association with the risk of colorectal cancer; this may help to predict the susceptibility of colorectal cancer in Chinese populations.